Þat vóro lavg munka. A Reading of Benedikts saga in Light of the Regula sancti Benedicti - Mauro Camiz (Boydell & Brewer Inc, 2021)
In addition to providing general evidence for the existence of a cult of St Benedict in medieval Iceland, this essay discusses the textual relations between Benedikts saga – the most complete Old Norse-Icelandic version of the widely circulated Vita beati Benedicti abbatis (BHL 1102), which forms part of Gregory the Great’s Dialogi – and the Regula sancti Benedicti, a collection of precepts for the governance of Benedictine monasteries. In the following, I consider the personal growth of St Benedict according to the legend and analyze individual episodes that are closely connected to specific precepts contained in the Regula. Subsequently, I focus on a small but noteworthy textual interpolation in Benedikts saga and discuss a significant omission, both of which appear to be deliberate editorial interventions on the part of the Norse compiler.